Effects of Uncertainity on Domestic Private Investments in Kenya - Mmeri, Ambetsa Nelson; Ongeri, B. Onkoba; Ndolo, David Katuta (European Scientific Journal, ESJ, 2023)
The domestic private investment serves as a prerequisite for the development and modernization of any economy. In Kenya, macroeconomic and political uncertainties play a significant role in influencing private domestic investments. That is informed by the fact that these investments allow investors to fund particular ventures, which creates jobs and increase government revenues through taxation, hence boosting the growth of the economy and improving the living standards of the people. However, private domestic investments are severely affected by both macroeconomic and political uncertainties with regards to how the government formulates political, economic, and regulatory policies that affect the business climate. Investors are risk-averse; hence they base investment decisions on prevailing and future conditions of the business environment. This study focused on analyzing the effects of uncertainty on Kenya’s domestic private investments. The study estimated the Autoregressive-Distributed Lag (ARDL) bounds technique which captures both short and long-run dynamics of this relationship amongst the variables. Time series data from UNCTAD, World Bank, and the Central Bank of Kenya for the period spanning 1980 to the year 2019 was used. The study results suggest that real GDP (RGDP) and real effective exchange rates (REER) have a significant and positive effect on private domestic investment (PDI). In contrast, inflation (INFL), Real interest rates (RINR), Political uncertainty (PRI), and WUIKEN (economic policy uncertainty and volatility in the stock markets) have a negative and significant effect on private domestic investments. Based on these results, the most significant factors affecting private domestic investments were found to be political uncertainty (PRI), real gross domestic investment (RGDP), and WUIKEN (economic policy uncertainty and volatility in the stock markets). Effectively, the study recommends that the government should enact policies that increase the ease of doing business and reduce economic and political uncertainty, such as a reduction in the tax rate, stabilization of exchange rate and stable political environment in order to reduce investor uncertainty and skepticism and also enhance their confidence.